2022
DOI: 10.1186/s12913-021-07390-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-savings and potential cost-savings through the distribution of generic antiretroviral drugs within the statutory health insurance market of Germany between January 2017 and June 2019

Abstract: Background Recent patent losses for antiretroviral drugs (ARV) have led to the debate of cost-saving through the replacement of patented drugs with generic drugs. The split of recommended single-tablet regimens (STR) into their single substance partners is one of the considerations mentioned in said debate. Particularly, generic tenofovir disoproxil/emtricitabine (TDF/FTC) is expected to hold untapped cost-saving potential, which may curb increasing overall expenditures for combined antiretrovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Generic substitution of ARVs was highly successful, which is consistent with international observations in other cohorts. Similar studies in countries such as France, Germany, and Italy have demonstrated comparable trends, indicating the potential generalizability of our ndings across certain European contexts [4,[15][16][17]. For instance, research conducted in Italy and France demonstrated that generic medication utilization led to signi cant cost savings in overall HIV expenditures [4,15].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Generic substitution of ARVs was highly successful, which is consistent with international observations in other cohorts. Similar studies in countries such as France, Germany, and Italy have demonstrated comparable trends, indicating the potential generalizability of our ndings across certain European contexts [4,[15][16][17]. For instance, research conducted in Italy and France demonstrated that generic medication utilization led to signi cant cost savings in overall HIV expenditures [4,15].…”
Section: Discussionsupporting
confidence: 72%
“…Germany's research has exhibited similar patterns regarding generic drug adoption and cost savings. Furthermore, they highlighted the additional cost-saving potential of splitting medication regimens, potentially reducing total expenditures by nearly 10% [17].…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the increasing costs of ARTs and the introduction of generic alternatives have led to a number of different strategies for cost reductions [15][16][17][18]. One of these methods is too de-simplify an STR to a TTR, usually containing a generic NRTI backbone [9,19].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 40% of cases with primary resistance showed reduced susceptibility to older drugs that are rarely used in Germany and that are no longer recommended for initial therapy [ 4 , 16 , 30 ]. This resistance is primarily based on the TAMs and the polymorphic E138A variant in NRTI resistance and the K103NS mutation in NNRTI resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of resistance due to substitutions at the K103 position is steadily increasing, a trend that has been observed and analyzed since 2014 in Germany [ 15 ]. Among drugs used in initial regimens, mutations that lead to pronounced resistance to the frequently prescribed non-TAM NRTIs (especially TDF/TAF, FTC, 3TC, ABC), as well as to PIs and INIs, are much more significant [ 30 ]. The frequency of these mutations is much lower and largely stable, ensuring sustained efficiency of the currently recommended primary regimens in the near future.…”
Section: Discussionmentioning
confidence: 99%